2021
DOI: 10.3389/fpsyg.2021.618105
|View full text |Cite
|
Sign up to set email alerts
|

Social Support, Attachment Closeness, and Self-Esteem Affect Depression in International Students in China

Abstract: With an increase in the number of international students in China, there has been a simultaneous increase in their emotional problems, such as depression, as well as the importance of their emotional well-being. This study aimed to investigate the influence of social support on depression and the mediation and moderation mechanisms of this relationship in international students. In total, 349 international students in China responded to a questionnaire survey comprising the Social Support Rating Scale, Self-ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
27
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(27 citation statements)
references
References 38 publications
0
27
0
Order By: Relevance
“…In total, after excluding 4 duplications and 75 unqualified researches, 11 articles were identified [ 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 ]. Among them, two investigated the learning condition and mental situation of international students in China under COVID-19 [ 15 , 17 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In total, after excluding 4 duplications and 75 unqualified researches, 11 articles were identified [ 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 ]. Among them, two investigated the learning condition and mental situation of international students in China under COVID-19 [ 15 , 17 ].…”
Section: Resultsmentioning
confidence: 99%
“…In total, after excluding 4 duplications and 75 unqualified researches, 11 articles were identified [ 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 ]. Among them, two investigated the learning condition and mental situation of international students in China under COVID-19 [ 15 , 17 ]. One focused on the psychological barriers that influence the efficiency of online education [ 15 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Based on this research, corresponding countermeasures and suggestions to improve employees' sense of organizational support, reduce turnover intention, and manage emotional labor were put forward. Research shows that good social support can enhance self-awareness, reduce psychological stress reactions, and moderate the negative impact of stressful events (Li et al, 2021 ).…”
Section: Theoretical Basis and Research Hypothesismentioning
confidence: 99%
“…Nevertheless, increasing numbers of international students do not necessarily imply that these students are content with their academic and non-academic experiences, nor do they imply whether these students are eager to endorse China as a terminus to other international students. Besides, a recent study revealed that as the number of international students increases in China, their emotional problems are also rising (Li et al, 2021). Researchers have recommended that given the economic and global importance of the international students, their experience should be considered as an issue of customer satisfaction (Wearring et al, 2015).…”
Section: Introductionmentioning
confidence: 99%